2018
DOI: 10.1111/tmi.13028
|View full text |Cite
|
Sign up to set email alerts
|

Quality of omeprazole purchased via the Internet and personally imported into Japan: comparison with products sampled in other Asian countries

Abstract: Abstractobjective To evaluate the quality of omeprazole personally imported into Japan via the Internet and to compare the quality of these samples with previously collected samples from two other Asian countries.methods The samples were evaluated by observation, authenticity investigation and pharmacopoeial quality analysis. Quality comparison of some selected samples was carried out by dissolution profiling, Raman spectroscopy and principle component analysis (PCA).results Observation of the Internet sites a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…The poor dissolution rates of the samples were a persistent problem, an observation which had previously been reported in our studies [56,57,60,61]. As an essential indicator of bioavailability and drug quality, the dissolution test has not been given as much attention as it deserves [58,62,63]. Despite the fact that all of the ESM samples contained the stated amount of API, a poor dissolution rate was observed in the buffer stage of the dissolution test in 10.9% of the ESM samples (Table 3; Figs.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The poor dissolution rates of the samples were a persistent problem, an observation which had previously been reported in our studies [56,57,60,61]. As an essential indicator of bioavailability and drug quality, the dissolution test has not been given as much attention as it deserves [58,62,63]. Despite the fact that all of the ESM samples contained the stated amount of API, a poor dissolution rate was observed in the buffer stage of the dissolution test in 10.9% of the ESM samples (Table 3; Figs.…”
Section: Discussionsupporting
confidence: 49%
“…The drug dissolution test is a good predicator for the sample performance test, while allowing observation of physicochemical changes in tablets/granules in capsules [57][58][59]. The results presented in this study demonstrate that 5.3% samples (95% CI, 0.021-0.086) were non-compliant (including all tested samples but excluding the falsi ed samples).…”
Section: Discussionmentioning
confidence: 77%
“…The poor dissolution rates of the samples were a persistent problem, an observation which had previously been reported in our studies 60 , 61 , 64 , 65 . As an essential indicator of bioavailability and drug quality, the dissolution test has not been given as much attention as it deserves 62 , 66 , 67 . Despite the fact that all of the ESM samples contained the stated amount of API, a poor dissolution rate was observed in the buffer stage of the dissolution test in 10.9% of the ESM samples (Table 3 ; Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we found that falsified weight-loss and erectile dysfunction drugs containing no active pharmaceutical ingredient [ 18 – 20 ]. Even when drugs are not falsified, the quality of a drug produced by the same manufacturer can differ according to the place of origin and market [ 21 ] In Southeast Asia, the circulation of low-quality metformin has been confirmed [ 12 ]. However, the quality and authenticity of metformin circulating on the Internet remain unclear.…”
Section: Introductionmentioning
confidence: 99%